2022
DOI: 10.1021/acsomega.2c06076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cyclotri- and Tetrasiloxanes with Pyrenyl Groups

Abstract: Cyclosiloxanes directly bearing polyaromatic groups on silicon atoms have scarcely been reported. Herein, hexa(1pyrenyl)cyclotrisiloxane (2) and octa(1-pyrenyl)cyclotetrasiloxane (3) were successfully prepared from di(1-pyrenyl)silanediol (1) in the presence of a weak base such as tetraethylammonium acetate and triethylamine in MeCN. The structure of the cyclosiloxanes bearing multiple pyrenyl groups in the solid and solution states was evaluated by NMR, X-ray crystallography, and density functional theory (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The product analysis revealed that the silanediol 1 a was condensed in the presence of these basic anions to yield the corresponding cyclotetrasiloxane ( 7 a ) as shown in Scheme 4 in MeCN at room temperature. Recently, we have reported the condensation of di(1‐pyrenyl)silanediol to give the corresponding cyclotrisiloxane ( 6 ) and cyclotetrasiloxane ( 7 ) in the presence of weak base such as AcO − or triethylamine at elevated temperature [24] . Therefore, the binding constants of 1 a for AcO − and H 2 PO 4 − could not be determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product analysis revealed that the silanediol 1 a was condensed in the presence of these basic anions to yield the corresponding cyclotetrasiloxane ( 7 a ) as shown in Scheme 4 in MeCN at room temperature. Recently, we have reported the condensation of di(1‐pyrenyl)silanediol to give the corresponding cyclotrisiloxane ( 6 ) and cyclotetrasiloxane ( 7 ) in the presence of weak base such as AcO − or triethylamine at elevated temperature [24] . Therefore, the binding constants of 1 a for AcO − and H 2 PO 4 − could not be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported the condensation of di(1pyrenyl)silanediol to give the corresponding cyclotrisiloxane (6) and cyclotetrasiloxane (7) in the presence of weak base such as AcO À or triethylamine at elevated temperature. [24] Therefore, the binding constants of 1 a for AcO À and H 2 PO 4 À could not be determined. However, UV-vis spectra of 1 a with less basic anions such as HSO 4 À , NO 3 À , ClO 4 À , Cl À , Br À , and I À showed smaller but reproducible spectral changes and small quenching of fluorescence spectra of 1 a due to the complexation with these anions.…”
Section: Anion Recognition By Silanediolsmentioning
confidence: 99%